Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan - Ashelby, Christopher W.; Lin, Wei-Cheng; Grave, Sammy De; Chan, Tin-Yam (Zootaxa, 2018)
The shrimp genus Palaemon Weber, 1795 and its related genera in Taiwan are reviewed based on newly collected specimens, whilst older records are critically reviewed. Five genera and 11 species are now known to occur in Taiwan, although there are no recent records for Palaemon modestus (Heller, 1862), which could be nationally extinct. The records of P. debilis Dana, 1852 and Nematopalaemon tenuipes (Henderson, 1893) in Taiwan are confirmed. Three genera, namely Brachycarpus Spence Bate, 1888, Leander Desmarest, 1849 and Leandrites Holthuis, 1950, each with one species are reported for the first time from Taiwan.